USING OF THE MODELS IN PRACTICE-ORIENTED EDUCATION DURING LEARNING OF PEDIATRIC DENTISTRY - L.F. Kaskova; N.V. Yanko; S.Ch. Novikova; L.F. Chupryna; A.V. Artemyev (Український стоматологічний альманах)
Teachers of clinical departments of establishments of higher medical education are faced with the problem of practical training of students, and many methods have been proposed for its improvement.